2011
DOI: 10.3344/kjp.2011.24.3.137
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Use of Ketamine on Post Operative Pain of Appendectomy

Abstract: BackgroundAlthough early reviews of clinical findings were mostly negative, there is still a widespread belief for the efficacy of preemptive analgesia among clinicians. In this study, we evaluated whether the preemptive use of ketamine decreases post operative pain in patients undergoing appendectomy.MethodsIn double-blind, randomized clinical trials, 80 adult male patients undergoing an operation for acute appendicitis were studied. Patients were randomly assigned to two groups. In the operating room, patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…They explained that this was because when a high dose of ketamine is administered, it can reach a relatively higher plasma concentration to suppress NMDA-R activation compared to that of low-dose administration. However, there are other reports in which 0.5 mg/kg of ketamine was helpful for relieving postoperative pain after abdominal surgery [18,19], and even that the analgesic requirement after cesarean section was reduced with administration of a low dose of 0.15 mg/kg [10,11]. There is also a report that the morphine requirement was not different in three groups of cesarean section patients administered 0.25, 0.5, or 1.0 mg/kg of ketamine [20]; thus, it is possible that the preemptive analgesic effect of ketamine is not dose dependent.…”
Section: Discussionmentioning
confidence: 99%
“…They explained that this was because when a high dose of ketamine is administered, it can reach a relatively higher plasma concentration to suppress NMDA-R activation compared to that of low-dose administration. However, there are other reports in which 0.5 mg/kg of ketamine was helpful for relieving postoperative pain after abdominal surgery [18,19], and even that the analgesic requirement after cesarean section was reduced with administration of a low dose of 0.15 mg/kg [10,11]. There is also a report that the morphine requirement was not different in three groups of cesarean section patients administered 0.25, 0.5, or 1.0 mg/kg of ketamine [20]; thus, it is possible that the preemptive analgesic effect of ketamine is not dose dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies [51–54] assessed a single dose of low‐dose ketamine using a reduction of pain as their first endpoint. This represents 251 patients, 141 of whom received ketamine.…”
Section: Methodsmentioning
confidence: 99%
“…Out of the four studies, two [51,53] reported a reduction of opioid consumption along with a reduction of pain scores for 24 hours postoperative. Safavi et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have reported varying results depending on the type of surgery. In gynecologic laparoscopic surgery, laparoscopic cholecystectomy and laparoscopic appendectomy, ketamine has preemptive analgesic effects, as seen during the early postoperative period [13,23,24]. In contrast, there are some reports showing that ketamine has no preemptive effect in cesarean sections and arthroscopic shoulder surgery [25,26].…”
Section: Discussionmentioning
confidence: 99%